Two series of Ln(iii)–Ag(i) heterometallic–organic frameworks constructed from isonicotinate and 2, 2′-biphenyldicarboxylate: synthesis, structure and photoluminescence properties1. Issue 20 (28th May 2015) - Lin, Xiao-Ming; Ding, Yu-Jia; Liang, Shui-Mei; Ge, Si-Xiao; Wei, Lei-Ming; Xie, Ji-Qing; Zhang, Gang; Cai, Yue-Peng
<x xml:space="preserve">Abstract</x> Two series of 2-D lanthanide–silver heterometallic–organic frameworks have been synthesized and their luminescent properties were also studied.